The Some Nutrient and Trace Elements Content of Wild Plants Using as Ethno botanical and Grown in the Gaziantep Region - Mustafa PEHLÄ°VAN, Hasan AKGUL, Fatih YAYLA (Journal of Applied Pharmaceutical Science, 2013)
This study was to determine some elements concentration in a few plant used as food. We were collected six different native plants in Gaziantep and its neighbor villages. These plants and their common names; Capsella bursa-pastoris L. (Shepherd's-purse), Rumex acetosella L. (Sheep's sorrel), Urtica dioica L. (Nettles), Portulaca oleraceae L. (Verdolaga), Malva neglecta Wallr. (Mallow) and Sinapis alba L. (Wild mustard). The collected samples were cleaned, cut, and dried at 105 â—¦C for 24 h. The samples were dissolved in 14 M HNO3 and residues were dissolved in 1 M HCl after diluated 50 ml ultra-pure water. After mineralization, the metals were determined using an atomic absorption spectrophotometer. We were investigated contents of some nutrient and trace elements (Cu, Pb, Zn, Mn, Co, K, Fe, Ca and Na) in these plants. According to result of our study, especially Portulacca oleraceae L. high concentration than other plants in terms of Cu, Pb, Zn and K. Highest Na concentration identified the Rumex acetosella L. but, Urtica dioica L. is least concentration than other plants in terms of all elements. We identified as the result of study, Portulaca oleraceae L. inclined to accumulation to heavy metals.
Keywords: Ethno botanic, Wildplants, Elements, Nutrient, Gazia